Does Higher Longevity Harm Economic Growth? - Sirag, Abdalla; Nor, Norashidah Mohamed; Law, Siong Hook (Panoeconomicus, 2019)
This study contributes to economic growth literature by providing new evidence on the relationship between life expectancy and economic growth utilising the recently developed dynamic panel threshold estimator. The sample of this study contains a total of 112 developed and developing countries covering the period from 1981 to 2010. The findings indicate the existence of a non-linear relationship between life expectancy and economic growth. In particular, life expectancy is useful for economic growth but only up to a certain threshold level; any further increase in longevity above the threshold would adversely affect growth. These findings emphasise the role of demographic transition in explaining the relationship between health and economic growth. Key words: Life expectancy, Demographic transition, Growth, Dynamic panel threshold. JEL: O47, J11, C23. Da li duži životni vek šteti ekonomskom rastu Ovo istraživanje doprinosi literaturi o ekonomskom rastu pružajući nove dokaze o vezi između očekivanog životnog veka i ekonomskog rasta koristeći nedavno razvijenu dinamičku procenu praga panela. Uzorak ove analize sadrži ukupno 112 razvijenih zemalja i zemlje u razvoju i obuhvata period od 1981. do 2010. godine. Rezultati ukazuju na postojanje nelinearne veze između očekivanog životnog veka i ekonomskog rasta. Konkretno, životni vek je koristan za ekonomski rast, ali samo do određenog nivoa; svako daljnje povećanje dugovečnosti iznad praga negativno bi uticalo na rast. Ovi rezultati naglašavaju ulogu demografske tranzicije prilikom objašnjavanja odnosa zdravlja i ekonomskog rasta. Ključne reči: Očekivani životni vek, demografska tranzicija, rast, prag dinamičkih panela.